What’s Up Doc (Strange)? A new glimpse of the Metaverse using NotebookLM AI - Cruz, M.; Oliveira, A.; Dias, R. (20th Iberian Conference on Information Systems and Technologies (CISTI 2025), 2025)
The convergence of Artiﬁcial Intelligence (AI), the Metaverse, and gaming is redeﬁning the landscape of digital interaction and innovation. This syn- ergy offers unprecedented opportunities for social engagement, economic growth, and the development of dynamic, immersive virtual worlds where gaming serves as a cornerstone, providing a rich and interactive medium for users to explore and experience new realities. This study aimed to contribute to understanding the Metaverse, Gaming and Immersion concepts using NotebookLM AI as a research Tool. This study aims to understand how this technology can analyze and project the concept of Metaverse and compare the NotebookLM analysis with text min- ing tool analysis. NotebookLM AI enhances research capabilities by delivering detailed and conclusive insights into the Metaverse.